Analysis of the Application of Interactive Flashcard Learning Media to Improve Learning Outcomes and Science Literacy in Elementary Schools (2019-2025) - Sofiana, Eli; Handoyo, Eko; Wardani, Sri; Subali, Bambang; Widiarti, Nuni (FKIP - Universitas Riau, 2025)
In line with the times and the needs of the world of education, the Merdeka Curriculum has been introduced as one of the government's efforts to improve the quality of learning in Indonesia. This article aims to analyze the application of interactive flashcard learning media in elementary schools, with a focus on the use of interactive flashcard learning media in the teaching and learning process, particularly in science subjects. The method used in this study is a literature review of 25 research journals related to the use of flashcards in learning in elementary schools. Based on the results of the literature analysis, it can be shown that the use of interactive flashcard learning media has a positive impact on the learning process, including improving learning outcomes and students' science literacy in science subjects. Flashcards have also been proven to be effective in helping students remember material and improve science literacy skills. In addition, flashcards can create a more enjoyable and interactive learning atmosphere, so that students participate more actively in learning activities. Thus, the application of this media is highly recommended as an alternative learning media in elementary schools.